New Data on the Anomalies of Tailless Amphibians of the Volga Basin - Fayzulin, A I; Chikhlyaev, I V; Mineev, A K; Kuzovenko, A E; Mihaylov, R A; Zaripova, F F; Popov, A I; Ermakov, O A (KnE Life Sciences, 2018)
This paper presents new findings on abnormal specimens of amphibians in the Volga basin. Some anomalies have been noted for the first time: macrophthalmia, eardrum anomalies in marsh frogs (P. ridibundus), the absence of a tympanic membrane in green toads and ectromelia in spadefoot Pallas samples (P. vespertinus).